ANALYSIS AND SIMULATION OF THE SPREAD OF COVID-19 IN INDONESIA USING SIR-FV MODELING WITH OPTIMIZATION - Alifianty Dinita Putri, Tafia
The COVID-19 virus pandemic in Indonesia has been going on since March 2020 and is still ongoing with conditions that need to be watched out for. This can be seen from the addition of daily active cases in Indonesia which is still changing dynamically. Alternative solutions that can analyze the prevention of the spread of the virus are modeling and simulation of the spread to estimate the pandemic conditions that may occur in Indonesia. The epidemiological-based modeling that is commonly used is the SIR modeling, which groups individuals into a certain number. Using this modeling and utilizing the concept of optimization technology, the modeling can be carried out more efficiently and accurately. In this final project, a model is developed, one of the SIR derivative models, namely SIR-FV, based on the concept of optimization to estimate and simulate various virus spread scenarios. There are 2 scenarios developed for analysis, namely the vaccination program scenario and the contact rate scenario. Based on the scenario simulation, it was found that the vaccination program could positively impact efforts to deal with the COVID-19 pandemic more effectively than the scenario without vaccination. The contact rate scenario also has a significant impact. However, the simulation results also show that if the vaccination program is not supported by adequate health protocols, then vaccination will not have impact on the prevention effort. Overall, it can be said that the developed model can function as needed, with MAPE reaching 0.012.